Pengaruh Kualitas Produk dan Distribusi Terhadap Penjualan Teh Poci - Asih Fitri Yanti; Fakhrurrazi Abbas; Moch Syauki (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2019)
In running a business, producers should know the market, where the products produced will be offered or marketed. These goals can be achieved by trying to maintain and increase profits or company profits. The data collection technique used in this study is field research conducted by circulating a list of statements to 81 respondents, namely consumers of the UMKM teh poci Yusrizal. Data processing was carried out with the help of the multiple regression equation model SPSS for Windows. The results of this study indicate that the product quality variable (X1) has a significant effect on increasing sales (Y), which is equal to 0.001. These results can be proved by the value of tcount> t table (12,419> 1,667). The distribution variable (X2) has no significant effect on increasing sales (Y), which is equal to 0.162. This can be proven by tcount <t table (1.410 <1.667) with a significant <0.05.